Lục xì : prostitution and venereal disease in colonial Hanoi - Vũ, Trọng Phụng, 1912-1939 (Southeast Asia--politics, meaning, memory., 2011)
In the late 1930's, Hanoi had a burgeoning commercial sex industry that involved thousands of people and hundreds of businesses. It was the center of the city's nightlife and the source of suffering, violence, exploitation, and a venereal disease epidemic. for Phung, a popular writer and intellectual, it also raised disturbing questions about the state of Vietnamese society and culture and whether his country really was "progressing" under French colonial rule.